2009
DOI: 10.1007/s00737-009-0089-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk behaviors for HCV- and HIV-seroprevalence among female crack users in Porto Alegre, Brazil

Abstract: Several studies have shown a high prevalence of HIV-seropositive status among crack users, though most refer to North American populations. Few studies evaluate HCV prevalence among female crack users. In addition, there is a particular lack of data about risk behaviors and HIV/HCV prevalence in this population around the world. In order to ascertain the HIV/HCV serostatus and associated risk behaviors for infection of female crack users of Porto Alegre, Brazil. A cross-sectional study of a convenience sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 36 publications
3
20
0
4
Order By: Relevance
“…In keeping with previous work on the topic,13,43,46,47 our findings highlight the positive impact that the support of family and friends who do not use substances can have on some women’s efforts to quit substances. Several participants seemed to find the group sessions useful in this regard, reporting that these group interventions offered them a new and positive social environment within which to seek support, facilitated the development of positive social networks, created capacity for leaving social contexts and relationships where substance use and victimization was promoted, and helped them feel empowered to take action to promote social change within their communities.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In keeping with previous work on the topic,13,43,46,47 our findings highlight the positive impact that the support of family and friends who do not use substances can have on some women’s efforts to quit substances. Several participants seemed to find the group sessions useful in this regard, reporting that these group interventions offered them a new and positive social environment within which to seek support, facilitated the development of positive social networks, created capacity for leaving social contexts and relationships where substance use and victimization was promoted, and helped them feel empowered to take action to promote social change within their communities.…”
Section: Discussionsupporting
confidence: 89%
“…Several participants in this study reported that they had to build positive social interactions and substance-free support systems to support their abstinence from substance use abstinence and replace their substance-using networks. This finding builds on previous work documenting the important influence of social drivers in facilitating abstinence from substance use 13,40,4346…”
Section: Discussionsupporting
confidence: 85%
“…This suggests a link between sexual promiscuity, unplanned pregnancies and prenatal cocaine exposure. International literature documents greater risky behaviors for sexually transmitted diseases among female crack users 7,8,19 . In our study, HIV seroprevalence in crack addicts was similar to the ones reported in other researches 20,21 (although these researches weren't conducted in pregnant women).…”
Section: Discussionmentioning
confidence: 99%
“…Global literature has documented the health-related harms, including infectious disease transmissions, associated with crack use practices (Dickson-Gomez, et al 2013, Von Diemen, et al 2010, Fischer, et al 2013). Although harm reduction strategies have been developed to reduce drug users’ health risks, few interventions are specifically tailored for crack smokers (Domanico and Malta 2012, Wechsberg, et al 2012).…”
mentioning
confidence: 99%